3-(2-Hydroxypheny1)-4-pheny1-1H-1,2,4-triazole-5(4H)-thione - Genç, S; Dege, N; Çetin, A; Cansiz, A; Sekerci, M; Dinçer, M (Int Union Crystallography, 2004)
The title molecule, C14H11N3OS, is non-planar. The phenyl and hydroxyphenyl rings form dihedral angles of 69.08 (9) and 24.57 (9)degrees, respectively, with the five-membered 2,4-dihydro-1,2,4-triazole ring. The molecules form centrosymmetric dimers through N-H...S hydrogen bonds, with an N...S distance of 3.279 (2) Angstrom. In addition, the molecule contains one O-H...N and one C-H...pi(phenyl) intramolecular interactions. The dimers are connected through weak intermolecular C-H...pi(hydroxyphenyl) interactions into chains in the a direction.